2019
DOI: 10.1002/cssc.201901211
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Non‐Thermal Plasma‐Assisted Nitrogen Fixation—Synergistic Catalysis

Abstract: In this Minireview, the multiple chemical synergies present in catalytic non‐thermal plasma‐assisted nitrogen fixation (NTPNF) are uncovered through a critical exploration of the underlying mechanisms, during which the catalyst, plasma, and reactants play different roles. For the gas‐phase NTPNF, the synergies consist of different aspects of the catalytic pathways such as electron‐impact dissociation; Zeldovich mechanism in the PNO interactions; and Eley–Rideal, Langmuir–Hinshelwood, surface adsorption, and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 103 publications
(231 reference statements)
0
34
0
Order By: Relevance
“…Research in this scientific field has revealed great potential and progress into using plasma technology to enable endothermic chemical reactions at low reactor temperatures, to improve the properties of catalysts and to synthesize renewable energy materials from greenhouse gases [4, 13 14]. So far different types of plasma technology [16][17][18][19][20][21][22][23][24][25][26] with or without catalysts have been tested on their performance compared to the traditionally thermal chemical processes. Especially a lot of work has been done on Dielectric Barrier Discharge (DBD) generated plasma to dissociate CO2.…”
Section: Introductionmentioning
confidence: 99%
“…Research in this scientific field has revealed great potential and progress into using plasma technology to enable endothermic chemical reactions at low reactor temperatures, to improve the properties of catalysts and to synthesize renewable energy materials from greenhouse gases [4, 13 14]. So far different types of plasma technology [16][17][18][19][20][21][22][23][24][25][26] with or without catalysts have been tested on their performance compared to the traditionally thermal chemical processes. Especially a lot of work has been done on Dielectric Barrier Discharge (DBD) generated plasma to dissociate CO2.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, various authors researched plasma-driven ammonia synthesis from CH 4 and N 2 (e.g., the feedstock for the SMR-based Haber-Bosch process), [133][134][135][136] as well as H 2 O and N 2 (e.g., the feedstock for the electrolysisbased Haber-Bosch process). [137][138][139][140][141][142] The challenge with using CH 4 , and even more with using H 2 O, is that the ammonia synthesis becomes endergonic. Although such a reaction can be driven by plasma, the energetically favourable reverse reaction is likely to compromise efficiency.…”
Section: Feedstocksmentioning
confidence: 99%
“…Extensive historical accounts can be found in other reviews. 82,84,90,141,261 The aim of this section is to show how recent insights in mechanisms can aid in the development of the field. The energy efficiency and conversion for various plasma reactor types are compared, describing the state of the art.…”
Section: Assessment Of Plasma-driven Ammonia Synthesismentioning
confidence: 99%
“…[7,8] Several methods of gas-phase NTPNF have been reported, where catalysts were used to improve the performance. [9] However, those methods are still limited by the low energy efficiency, for the nitrogen containing products may partially be decomposed once they are formed in the reactive plasma region, which restricts the nitrogen fixation yield and energy efficiency. [9,10] To overcome this shortcoming, gas-liquid NTPNF is of great interest, as the nitrogen compounds (NH 4 + , NO 2 À NO 3 À ) are directly produced from N 2 and H 2 O, and at the same time the nitrogen fixing products can dissolve in water to avoid decomposition in plasma ( Figure 1).…”
mentioning
confidence: 99%
“…[9] However, those methods are still limited by the low energy efficiency, for the nitrogen containing products may partially be decomposed once they are formed in the reactive plasma region, which restricts the nitrogen fixation yield and energy efficiency. [9,10] To overcome this shortcoming, gas-liquid NTPNF is of great interest, as the nitrogen compounds (NH 4 + , NO 2 À NO 3 À ) are directly produced from N 2 and H 2 O, and at the same time the nitrogen fixing products can dissolve in water to avoid decomposition in plasma ( Figure 1). [11] In most of the recent studies on gas-liquid NTPNF, a "pin-toplate" design was adopted, [11,12] where reactions occurred at the small contact area between the plasma jet and the water surface, and only a volume of 10-20 mL can be accommodated by such reactors.…”
mentioning
confidence: 99%